2019
DOI: 10.5194/hess-23-1667-2019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of glacier loss and vegetation succession on annual basin runoff

Abstract: Abstract. We use a simplified glacier-landscape model to investigate the degree to which basin topography, climate regime, and vegetation succession impact centennial variations in basin runoff during glacier retreat. In all simulations, annual basin runoff initially increases as water is released from glacier storage but ultimately decreases to below preretreat levels due to increases in evapotranspiration and decreases in orographic precipitation. We characterize the long-term (> 200 years) annual basin r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Figure 6a shows melt-flux changes following a trend in mass balance (and therefore specific melt), with L ( t ) given by the RB14 model for the idealized glaciers. M g peaks at t ~ τ for both glaciers (peaks are at 15 and 49 years), consistent with Carnahan and others (2019). The role of the response time is conceptually straightforward: for long τ , a slower initial retreat means specific melt anomalies can increase more before much melt area is lost, and the peak in M g is thus later than for short τ .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Figure 6a shows melt-flux changes following a trend in mass balance (and therefore specific melt), with L ( t ) given by the RB14 model for the idealized glaciers. M g peaks at t ~ τ for both glaciers (peaks are at 15 and 49 years), consistent with Carnahan and others (2019). The role of the response time is conceptually straightforward: for long τ , a slower initial retreat means specific melt anomalies can increase more before much melt area is lost, and the peak in M g is thus later than for short τ .…”
Section: Resultssupporting
confidence: 90%
“…This phenomenon depends fundamentally on transient glacier dynamics. Carnahan and others (2019) showed that, over a wide range of parameters, the peak in simulated glacier-melt runoff occurred ~1 τ after the onset of a climate trend, using a metric for τ very similar to Eqn (1) (see Harrison and others, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…One of the most conspicuous of the anticipated effects will be the altered production of meltwater (e.g., Milner et al, 2017;Huss and Hock, 2018), along with associated changes in hydrologic pathways (e.g., meltwater generated further inland and at greater elevations, intensifying connectivity between supra-and subglacial habitats), which ultimately have the greatest relevance for determining the quantity and character of solute and particulate fluxes. Yet, while the physical and chemical changes accompanying deglaciation may be comparatively straightforward to predict, the biological consequences for glacial ecosystems are far less intuitive (Fell et al, 2017;Hotaling et al, 2017a), and generalizations are inherently difficult to make due to differences in glacier size, elevation, bedrock, thermal regime, vegetation, and precipitation patterns (e.g., Carnahan et al, 2019). By studying microbial assemblages exported by glacier meltwater streams, it may be possible to investigate microbial processes taking place in the overall glacial system, and assess changes in structure and export over time.…”
Section: Discussionmentioning
confidence: 99%
“…We model changes in glacier geometry with a onedimensional form of the shallow shelf approximation (SSA), which is a depth-and width-integrated flow model (Nick et al, 2009;Enderlin et al, 2013;Carnahan et al, 2019). For our simulations, we use a glacier with a simple bed geometry (a uniformly sloping bed with a slope of 4 • ) and assume a simple climate parameterization.…”
Section: Glacier Evolutionmentioning
confidence: 99%